PERAN PROTEIN PILI 11 kDa Streptococcus pneumoniae SEBAGAI PROTEIN HEMAGLUTININ DAN ADHESIN - Mufida, Diana Chusna; Salsabila, Yuna Annisa; Suswati, Enny; Hermansyah, Bagus; Agustina, Dini (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2020)
Role of Pili Protein 11 kDa ofÃ‚Â Streptococcus pneumoniaeÃ‚Â as HemagglutininÃ‚Â and Adhesin ProteinÃ‚Â Streptococcus pneumoniae has pili which play roles in adhesion, colonization of nasopharyngeal epithelial cells, and phagocytic inhibition of immune cells. This study aimed to determine the characteristics of the 11 kDa pili protein as hemagglutinin and adhesin, as well as their immune responses. The 11 kDa pili protein from S. pneumoniae was isolated by SDS-PAGE, purified by electroelution and dialysis. Hemagglutination and adhesion tests were carried out on the protein, and western blotting of the polyclonal antibody immune responses were evaluated. Hemagglutination test showed that the 11 kDa pili protein played a role in the hemagglutination process up to 2-time dilution. Adhesion test showed there was a correlation between the dose of the protein and the bacteria attached to the epithelial cells. The Pearson correlation test showed a P value of 0.010 and a correlation coefficient of R = -90.919. Quadratic regression test produced R2 = 0.974. Western blotting test showed that 11 kDa pili protein polyclonal antibodies recognized 67 kDa and 11 kDa pili proteins. The study concluded that the 11 kDa S. pneumoniae pili protein acted as hemagglutinin and adhesin, and the polyclonal antibody protein responded to 67 pDa and 11 kDa BM pili proteins.Keywords: adhesin, hemagglutinin, pili, protein 11 kDa, Streptococcus pneumoniaeÃ‚Â ABSTRAKStreptococcus pneumoniae memiliki pili yang berperan dalam adhesi, kolonisasi sel epitel nasofaring, serta sebagai inhibitor fagositosis sel imun. Penelitian ini bertujuan mengetahui karakteristik protein pili 11 kDa sebagai hemagglutinin dan adhesin serta respons imunnya. Protein pili 11 kDa dari bakteri S. pneumoniae diisolasi secara SDS-PAGE, dipurifikasi dengan elektroelusi dan dialysis. Uji hemaglutinasi dan adhesi dilakukan pada protein tersebut, serta dievaluasi respon imun poliklonal antibodinya secara western blotting. Uji hemaglutinasi menunjukkan protein pili 11 kDa berperan dalam proses hemaglutinasi hingga pengenceran 2 kali. Uji adhesi menunjukkan korelasi antara dosis protein dan bakteri yang menempel pada sel epitel. Uji korelasi Pearson menunjukkan P value 0,010 dan koefisien korelasi R = -0,919. Uji regresi Quadratic menghasilkan R2 = 0,974. Uji Western blotting menunjukkan antibodi poliklonal protein pili 11 kDa mengenali protein pili 67 kDa dan 11 kDa. Penelitian ini berkesimpulan protein pili 11 kDa S. pneumoniae berperan sebagai hemaglutinin dan adhesin, serta antibodi poliklonal protein tersebut memberi respons terhadap protein pili BM 67 kDa dan 11 kDa.Ã‚Â